Root inoculation of green bell pepper (Capsicum annum) with Bacillus amyloliquefaciens BBC047: effect on biochemical composition and antioxidant capacity. (14th May 2019) - Cisternas‐Jamet, Jonathan; Salvatierra‐Martínez, Ricardo; Vega‐Gálvez, Antonio; Uribe, Elsa; Goñi, María G; Stoll, Alexandra
Abstract: BACKGROUND: Consumption of bell peppers is recommended because of their bioactive compound content and their positive effects on health. Growth‐promoting rhizobacteria are popular because of their ability to promote plant growth by improving the fixation of nutrients or by inducing a systemic response. Green bell pepper ( Capsicum annum ) roots were inoculated with an autochthonous strain of Bacillus amyloliquefaciens, at different stages of development: T1, inoculation in the seedbed before transplant; T2, inoculation at and after transplant; T3, inoculation in the seedbed, at and after transplant. Bell pepper plants without inoculation were considered as control. Physicochemical composition and antioxidant activity of the fruits were measured to select the best treatment. RESULTS: T1 increased crude proteins, fat, Ca, Fe, vitamin C, total phenolic content, antioxidant capacity by DPPH and by ORAC. On the other hand, T1 decreased reducing sugars, K and Cu content. No significant differences for total carbohydrates, ash and photosynthetic pigments were found. CONCLUSION: Inoculated green bell peppers have enhanced its functional value and could be considered as an important source of bioactive compounds with elevated antioxidant activity. © 2019 Society of Chemical Industry